The little mermaid - Daynes, Katie; Andersen, Hans Christian, 1825-1885.; Marks, Alan, 1957- (London : Usborne, 2006)
Hans Christian Andersen's classic fairy tale of a little mermaid who falls in love with a human prince.
"From the story by Hans Christian Andersen"--Cover.
4.0
K-3
Keywords: Fairy tales; Mermaids -- Fiction; Princes -- Fiction; Fairy tales; Mermaids and mermen -- Fiction; Princes -- Fiction